2022
DOI: 10.1002/etc.5315
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate Species for the Bioavailability and Accumulation Assessment of Manufactured Polymer‐Based Nano‐ and Microplastics

Abstract: Bioaccumulation tests with invertebrates have recently been discussed as a suitable alternative to bioaccumulation tests with metal‐ or metal oxide‐based nanoparticles in fish for regulatory assessment. In the present study, as a first step, we investigated the suitability of three invertebrate species for bioaccumulation tests with nano‐ and microplastics. In a laboratory approach the freshwater bivalve Corbicula fluminea, the freshwater amphipod Hyalella azteca, and the terrestrial isopod Porcellio scaber we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 64 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Fagiano et al (2023) found that marine sediments hold two-fold microplastics than sea surface waters and are dominated by fibers. Bioconcentration of MPs is supported by previous studies in marine invertebrates (Sfriso et al, 2020;A ́lvarez-Ruiz et al, 2021;Kuehr et al, 2022). In the case of sea cucumbers, bioconcentration has been hypothesised by other authors (Iwalaye et al, 2020;Lombardo et al, 2022;Martines et al, 2023) and confirmed in the genus Apostichopus (Mohsen et al, 2022).…”
Section: Discussionmentioning
confidence: 52%
“…Fagiano et al (2023) found that marine sediments hold two-fold microplastics than sea surface waters and are dominated by fibers. Bioconcentration of MPs is supported by previous studies in marine invertebrates (Sfriso et al, 2020;A ́lvarez-Ruiz et al, 2021;Kuehr et al, 2022). In the case of sea cucumbers, bioconcentration has been hypothesised by other authors (Iwalaye et al, 2020;Lombardo et al, 2022;Martines et al, 2023) and confirmed in the genus Apostichopus (Mohsen et al, 2022).…”
Section: Discussionmentioning
confidence: 52%
“…Two studies have specifically investigated the ingestion of MPs by terrestrial isopods. Kuehr et al (2022) studied whether manufactured nanoplastics and MPs accumulated in P. scaber . There were no observed instances of accumulation of MPs in the isopods after 14‐day exposures (Kuehr et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kuehr et al (2022) studied whether manufactured nanoplastics and MPs accumulated in P. scaber . There were no observed instances of accumulation of MPs in the isopods after 14‐day exposures (Kuehr et al, 2022). Wood and Zimmer (2014) assessed the ability of P. scaber to consume biodegradable plastics.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the BCF of nanoplastics in E. crassipes reached 306.5 after 8 weeks of exposure, which is hundreds of times higher than those in crop pants (1.8~2.9). Previous studies have investigated the bioaccumulation of micro-and nanoplastics by various aquatic organisms, including invertebrates (Kuehr et al, 2022), zooplankton (Rist et al, 2017), zoobenthos (Redondo-Hasselerharm et al, 2021), shellfish (Al-Sid-Cheikh et al, 2018), as well as with fish species (Kim et al, 2021). Although it is difficult to compare the bioaccumulation in different organisms, floating plants like E. crassipes show a higher 'plastic particle trapping' potential than submersed or emersed plants under similar exposure concentrations of plastic particles.…”
Section: Discussionmentioning
confidence: 99%